2005
DOI: 10.1159/000086784
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells and Vascular Endothelial Growth Factor in Colorectal Cancer: Correlations with Clinicobiological Findings

Abstract: Objective: Dendritic cells (DC) are central to the development of immune system responses. In a cohort of 54 patients affected by colorectal cancer, we prospectively investigated the number of peripheral blood (PB) DC type 1 (DC1) and type 2 (DC2) and correlated their counts and functionality to the stage of the disease and to vascular endothelial growth factor (VEGF) levels. Results: At diagnosis, compared with healthy controls, patients presented reduced PBDC1 and PBDC2 numbers (p < 0.001). Moreover, in canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 57 publications
6
36
0
1
Order By: Relevance
“…Notably, the DC profiles at baseline were similar to those of the healthy subjects, suggesting that in our population no critical impairment in immune surveillance against tumour was evidenced, unlike previous experienced [25,26], even if in CRC patients [27]. …”
Section: Discussionsupporting
confidence: 61%
“…Notably, the DC profiles at baseline were similar to those of the healthy subjects, suggesting that in our population no critical impairment in immune surveillance against tumour was evidenced, unlike previous experienced [25,26], even if in CRC patients [27]. …”
Section: Discussionsupporting
confidence: 61%
“…Several lines of evidence indicate that the ability of tumors to affect DC maturation and differentiation may result in a generalized failure of the host to mount an effective antitumor response. These findings and additional data (5,(7)(8)(9) are relevant clinically, as an association with significantly poorer prognoses in patients with several types of cancer has been described. Although these observations suggest that DC play a critical role in determining the final outcome of the immune response, the mechanisms responsible for this phenomenon remain uncharacterized, and the effects of tumors on DC function are poorly understood.…”
Section: Endritic Cells (Dc)mentioning
confidence: 53%
“…This, in turn, suggests that the release of soluble factors by the tumors contributes to the tumor-associated alterations in the activity of DC. Several reports have now confirmed that the release of IL-10, IL-6, macrophage colony-stimulating factor, vascular endothelial growth factor, and gangliosides and/or prostanoids by tumors can prevent DC differentiation and function in vitro and in vivo (7,(11)(12)(13)(14)(15).…”
Section: Endritic Cells (Dc)mentioning
confidence: 92%
“…Similarly, the percentage of both DC populations in peripheral blood was significantly lower in patients with NSCLC than in the control group, while in patients with breast cancer, the number of 'lymphoid' DC was significantly higher than in NSCLC patients [111]. In a cohort of 54 patients affected by colorectal cancer, investigation of the number of peripheral blood DC type 1 (DC1, myeloid DC, conventional DC) and type 2 (DC2, lymphoid DC, plasmacytoid DC) revealed that in comparison to healthy controls, patients presented reduced DC1 and DC2 numbers [112]. Moreover, in cancer patients, DC showed low levels of HLA DR, CD11c, CD83, CD86, Ovarian cancer Attraction of plasmacytoid DC, which induce regulatory CD8+ T cells and induce angiogenesis, CXCL12 protects tumor plasmacytoid DC from apoptosis [184,199] and Mannose receptor, an up-regulation of CXCR4 and a reduced T-cell stimulation capability [112].…”
Section: Regulation Of Intratumoral Dendritic Cells By Cytokines Chementioning
confidence: 99%